Factors affecting visual outcomes of pituitary macroadenoma following transsphenoidal surgery - Shoeb; Ugan Singh Meena; Suresh Kumawat (Romanian Neurosurgery)
Objective: 1. To provide quantitative objective measurement of the efficacy of surgery for pituitary macroadenoma. 2. To discuss different factors that could affect visual outcomes of pituitary macroadenoma